Formação e sexualidade: um estudo a partir dos relatos dos estudantes de difererentes cursos de Psicologia - Senem, Cleiton José [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Sexuality is a fundamental dimension in the human being's life, from birth to old age. It is inherent in human nature, presenting different manifestations throughout history and receiving several forms and meanings. Sexuality is constituted of imbricate dimensions: biological, cultural, and psychological. When we observe the different ways people have lived sexuality thoughout history, it is possible to identify matriarchal and patriarchal models, moments of greater openness and freedom, as well as phases of repression, fear, and mistrust. Sexuality is the object of several sciences and Psychology also, since these professionals work directly with this issue in all their activities, in the clinic, organization, school, and community. Therefore, they must be prepared to openly address the issues concerning such topic, with no prejucice, developing actions that are constructive, critical, and systematic and helping people and groups to reflect on this issue. Thus, the purpose of this study was to investigate the reports of Psychology students on sexuality, considering the implications of the course on their personal and professional training. The participants of the research were 11 fourth-year Psychology students (8th semester), from three different institutions, who answered a semi-structured questionnaire. The results indicate that students have a wide and complex understanding of sexuality, considering its biological, cultural and psychological dimensions. At the same time, the reproduction of a patriarchal conception of sexuality could be identified both in the answers provided by men and women. A different of perception was found among the different institutions: while participants of the private universities showed themselves to be more conservative, the participants of the public university showed themselves to be more liberal. It is also possible to identify that, although all courses approach the topic in its formative process...

A sexualidade é uma dimensão fundamental na vida do ser humano, desde o nascimento até a velhice. Ela é inerente a natureza humana, apresentando diferentes manifestações ao longo da história, recebendo inúmeras formas e significados. Ela se constitui por dimensões imbricadas: biológicas, culturais e psíquicas. Ao observar as diferentes formas como as pessoas a viveram ao longo da história, é possível identificar modelos matriarcais e patriarcais, momentos de maior abertura e liberdade, assim como fases de repressão, medo e desconfiança. A sexualidade é objeto de estudo de várias ciências e também da psicologia, cujos profissionais trabalham diretamente com esta questão em todas as suas atividades seha na clínica, na organização, na escola e na comunidade. Por isso, precisam estar preparados para abordar as questões relativas ao tema de forma aberta, sem preconceito, desenvolvend ações construtivas, críticas e sistemáticas, auxiliando as pessoas e os grupos a refletirem sobre tal questão. Nesse sentido, o objetivo desta pesquisa foi investigar os relatos dos estudantes de psicologia sobre sexualidade, considerando as implicações do curso sobre sua formação pessoal e profissional. Participaram da pesquisa 111 estudantes de psicologia, do quarto ano (8ª semestre), de três diferentes instituições, que responderam um questionário semiestruturado. Os resultados obtidos indicam que os estudantes possuem uma compreensão ampla e complexa de sexualidade, considerando sua dimensão biológica, cultural e psíquica. Ao mesmo tempo, pode-se identificar a reprodução de uma concepção patriarcal de sexualidade, tanto nas respostas fornecidas pelos homens quanto pelas mulheres. Constatou-se também uma diferença de percepção entre as diferentes instituições: enquanto os participantes das universidades particulares demonstram-se mais conservadores, os participantes da universidade pública demonstraram ser mais...
Training and sexuality: a study based on the report of students of different psychology courses
Keywords: Sexo; Psicologos - Formação; Educação sexual; Sex